Reproductive and sexual Health of surrogate mothers, developing a care program: a protocol for mixed methods study - Marjan Goli; Ziba Farajzadegan; Zeinab Heidari; Shahnaz Kohan (BMC, 2019)
Abstract Background Gestational surrogacy is one of the options for women whom pregnancy is contraindicated. Despite of increasing demand for gestational surrogacy, its various aspects are controversial. The unique nature of surrogacy causes surrogate mothers to face a variety of problems such as, ethical confusion, psychological disturbance and reproductive health matters. Therefore, it is necessary to develop a comprehensive care program for reproductive and sexual health providing specific care at prenatal and pregnancy as well as delivery and postpartum period in socio- cultural context of Iran. Methods This research is an exploratory study with the qualitative-quantitative sequencing design (mixed) that is consisted of three sequential phases. In the first phase, following a qualitative approach, the researcher will explain needs of reproductive and sexual health in surrogate mothers. In the second phase, a primary reproductive and sexual health care program is designed for surrogate mothers in which, in addition to using the qualitative study results, related papers and texts will be also used. In the third phase of the study, reproductive and sexual health care program will be evaluated by RAND method (RAM). Discussion The results of this mixed method study are expected to lead to the development of a reproductive and sexual health care program meeting the needs of surrogate mothers and are in accordance with the cultural conditions of the research community, ultimately leading to improvement in reproductive and sexual health of surrogate mothers.